Relationship of METS-IR with cardiometabolic multimorbidity in China: a nationwide longitudinal cohort study - Zhou, Chunyan; Zhang, Yanyu; Liu, Xiaoyi; He, Chenyu; Li, Shiyang (Frontiers in Nutrition, 2025)
BackgroundCardiometabolic multimorbidity (CMM) has emerged as a global health challenge with a high mortality risk. This study aimed to explore the association between the metabolic score for insulin resistance (METS-IR) and the incidence of CMM.MethodsThis study included 6,977 individuals in the CHARLS database. We used multiple cox proportional hazards regression and restricted cubic splines (RCS) analysis to evaluate the association between METS-IR and CMM. Subgroup analyses and interaction tests were also performed.ResultsDuring a median 109 (108–109) months of follow-up, 745 (10.7%) participants were diagnosed with new-onset CMM. The incidences of CMM among participants in quartiles (Q) 1–4 of METS-IR were 4.99, 7.51, 10.67, and 19.54%, respectively. METS-IR was significantly higher in individuals with CMM compared to those without CMM (p < 0.001). After multivariate adjustment, a higher METS-IR was significantly associated with an increased risk of CMM. Compared to participants in Q1 of METS-IR, the hazard ratios (HRs) (95% confidence intervals [CIs]) using cox proportional hazards regression analysis for those in Q2–4 were 1.52 (1.15–2.00), 2.02 (1.56–2.63), and 3.61 (2.80–4.64), respectively. RCS analysis revealed a significant nonlinear association between METS-IR and CMM (nonlinear p < 0.05). The association between METS-IR and the incidence of CMM was present in almost all the subgroups. Furthermore, the predictive ability of METS-IR for CMM was 0.669, which surpassed that of both the triglyceride to high-density lipoprotein cholesterol ratio and the triglyceride glucose index.ConclusionA higher METS-IR was closely associated with an increased risk of CMM. Further studies on METS-IR could be beneficial for preventing and treating CMM.